Utilizing Demographic, Ethnic, and Human Emotional Variables to Enhance Compassion Feeling: Basis for Slow Lorises Conservation Extension Media Development - Christine, Wulandari; Nurhaida, Ida; Sugeng Prayitno , Harianto; Andi, Windah; Samsul, Bakri (Jurnal Manajemen Hutan Tropika, 2026)
Slow lorises, listed as endanger under CITES Appendex I, are increasingly found outside forest habitate, including the buffer zone of Wan Abdul Rachman Grand Forest Park (Tahura WAR) in Lampung Province. While this coexistence support ex-situ conservation, it also raises risks of illegal hunting and trafficking. This study investigates how demographics, education, ethnicity, and emotion influence compassion (COMP) toward slow lorises. A log-linear model was applied at a 95% confidence level.  The response variable [COMP] was scored as 1 if respondents expressed compassion, and 0 otherwise. Explanatory variables included esmotions (affection, neutral, disgust), prior direct sightings, education level, and ethnic background. Data were collected through door-to-door survey of 150 respondents across three villages in the Tahura WAR buffer zone during October–November 2023. Each respondent was shown a 20 cm × 30 cm photograph of slow loris before answering. Results suggest that compassion increases significantly among women, those with fisthand sightings, high school gradustes, and respondents with Lampung or Sundanese parental backgrounds. Affection strongly boost COMP, while digust reduces it. These findings highlight the importance of fostering empathy through conservation education programs that complement law enforcement. These results also support the SDG 15 and 16 pillars implementation.